2022
DOI: 10.3390/jof8050503
|View full text |Cite
|
Sign up to set email alerts
|

[20(22)E]-Lanostane Triterpenes from the Fungus Ganoderma australe

Abstract: Twelve new lanostane triterpenoids (1–5, 7–13) were isolated from the fruiting bodies of the fungus Ganoderma australe. The structures of the new compounds were elucidated by extensive 1D and 2D NMR, and HRESIMS spectroscopic analysis. All the triterpenes are featured by 20(22)E configurations which are uncommon in the Ganoderma triterpene family. The absolute configuration of the C-25 of compounds 1, 2, and 6 were determined by the phenylglycine methyl ester (PGME) method. A postulated biosynthetic pathway fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The key intermediate lanosterol is biosynthesized from squalene, the common precursor of triterpenes. Further oxygenation on multiple sites of the lanosterol leads to the key intermediate A [ 19 , 20 ]. Abstraction of the proton of OH-20 by the retro-aldol reaction (route A) give compound 1 , which has been further oxygenated at C-6 position to yield 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The key intermediate lanosterol is biosynthesized from squalene, the common precursor of triterpenes. Further oxygenation on multiple sites of the lanosterol leads to the key intermediate A [ 19 , 20 ]. Abstraction of the proton of OH-20 by the retro-aldol reaction (route A) give compound 1 , which has been further oxygenated at C-6 position to yield 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Peng et al reported on anti-adipogenic lanostane-type triterpenoids from the edible mushroom Ganoderma applanatum, which is utilized for medical purpose [54]. Other lanostane-type metabolites are presented from the species Ganoderma australe by Lin Zhou [55].…”
mentioning
confidence: 99%